Kualitas dan Kesuksesan Implementasi Sistem Pelaporan Nilai di Sekolah Menengah Atas Dengan Menggunakan Expectation-Confirmation Model dan DeLone & McLean - David Tria Utama; Admaja Dwi Herlambang; Himawat Aryadita (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The e-report card value reporting system is used by high school to manage student grades. However, in operation there are still complaints from users of the system such as failing to function the print value causes the withdrawal of student report cards and system bugs when the value that should not exist but the system gives a value of 0. This study aims to evaluate the quality and success of the e-report card school for the continued implementation of e-report cards based on the Expectation-Confirmation Model and DeLone & McLean Model models. Data obtained by distributing questionnaires and interviews as supporting the results of the questionnaire. The sample used in this study was a saturated sample with 39 respondents from the curriculum, homeroom and school admin. The results of this study indicate the level of quality of e-report card system is 80.8%. In the Perceived of Usefulness variable, it is in the high category (83.2%), Confirmation is in the high category (80.4%), Satisfaction is in the high category (75%) and IS Continuance Intention is in the high category (84.6% ). The success rate of the e-report card system is 74.5%. In the Information Quality variable included in the high category (74.2% ), Quality System included in the high category (75.2% ), Service Quality variables included in the high category (60.8%), Use variables included in the high category (72% ), variables User Satisfaction is in the high category (80% ) and the Net Benefit variable is in the high category (85.2% ). Quality improvement recommendations will be given to the Confirmation and Satisfaction variable because it is below the total variable average. Then recommendations for increasing success will be given to the Information Quality, Service Quality and Use variables because they are below the total variable average.